The culture of democracy a sociological approach to civil society - Xu, Bin (Cultural sociology)
"The Culture of Democracy provides the first systematic survey of the cultural sociology of civil society and offers a committed global perspective. It shows that, as everyone is eager to have their voice heard, cultural sociology can serve as an "art of listening," a thoroughly empirical approach that takes ideas, meanings, and opinions seriously, for people to contemplate significant theoretical and public issues." --Provided by publisher.